Statistical Misconceptions, Awareness, and Attitudes towards Open Science Practices in Slovak Psychology Researchers - Rajčáni, Jakub; Vargová, Lenka; Adamkovič, Matúš; Kačmár, Pavol (Studia Psychologica, 2023)
In the years following the reproducibility crisis in behavioral sciences, increased attention of the scientific community has been dedicated to the correct application of statistical inference and promotion of open science practices. In the present survey, we contacted psychology researchers, lecturers, and doctoral students from all universities in Slovakia and the Slovak Academy of Sciences via email. Together we received answers from 65 participants. Questions in the survey covered the most common misconceptions about statistical hypothesis testing, as well as awareness, attitudes, and barriers related to the adherence to open science practices. We found a high prevalence of statistical misconceptions, namely related to the interpretation of p-values and interpretation of null results. At the same time, participants indicated mostly positive attitudes towards open science practices, such as data sharing and preregistration, and were highly interested in further training. These results provide an insight into the needs of the Slovak psychology research community. This is an important step in the further dissemination of open science practices and the prevention of common statistical and methodological errors.